Factors Influence on E-procurement Adoption in Tea Processing Factories in Sri Lanka - Bandara, Wickrama Arachchillage Ayomi Menaka; Athapaththu, Jayani Chamarika (International Journal of Supply Chain and Logistics, 2024)
Purpose: Information communication technology (ICT) to handle transactions, is widely used across many industries, yet factors influencing its adoption, particularly in tea industry in developing countries like Sri Lanka, have been overlooked. This study aims to identify the factors influencing on digitization of the procurement in tea processing factories in Sri Lanka. Methodology: The study relies on a quantitative research approach using a survey design. Rathnapura district, was selected as it is the largest law country tea growing district and sample of fifty factory staff members were selected using convenience sampling technique. Data was analyzed by use of the Statistical Package of Social Sciences. Findings: Questionnaire survey results revealed that user friendliness and top management support have a significant and positive impact on e-procurement adoption while perceived benefits, ICT literacy and environmental factors not having a statistically significant impact on e-procurement adoption. Unique contribution to theory, practice and policy: Study provides recommendation to achieve higher degree of adoption and successful implementation of e-procurement technology among tea processing factories in Sri Lanka.